(untitled) (Global Journal of Human-Social Science, 2024)
The article is about the influence of Spanish in the US through sports information There was a first moment related to the first emigration in the search for that first American dream Today professionals come from a more globalized environment Among the levels the lexicalsemantic level plays an important role with a trend in recent years towards leveling American sports information in Spanish currently exerts an influence on the rest of society